“I Came Because I Knew It Was Geared Towards Queer People”: A Queer and Trans Youth-Led Workshop on Sexuality Education - Moni Sadri; Vanessa Oliver (Social Sciences)
This paper details how, in partnership with young people, community workshops centred on queer joy can offer queer and trans youth sexuality education (SE) that is relevant to their experiences, lived realities, and desires. In the data, young people discuss how tailored content, queer pedagogies, youth-centric approaches, and affirming spaces that are responsive to their questions might improve their sexuality knowledge as well as their mental health. A total of 22 youth participants from a mid-size Canadian city, the vast majority of whom identified as queer and/or trans, registered in a weekend workshop to evaluate SE video lessons created by educators enrolled in our partner organization’s sexuality education training program. Through this process, young people leaned on both their expertise and experience to critically reflect on the content and pedagogies employed by the educators. Additionally, 14 youth participated in post-workshop interviews where they continued these conversations and reflected on their SE experiences. In contrast to queer and trans young people’s more violent experiences in classrooms, public spaces, and political discourses, this community intervention workshop cultivated community, knowledge, power, and solidarity between and among youth participants. As they used and created memes to laugh in the face of structures and situations that attempt to erase their bodies and experiences, young people reached for a vision of sexuality education that not only includes them but centres on their desires and curiosities.